Makeshift freedom seekers: Dutch travellers in Europe, 1815-1914 - Geurts, APH (2013)
This thesis questions a series of assumptions concerning the nineteenth- and early-twentieth-century modernization of European spaces. Current scholarship tends to concur with essayistic texts and images by contemporary intellectuals that technological and organizational developments increased the freedom of movement of those living in western-European societies, while at the same time alienating them from each other and from their environment. I assess this claim with the help of Dutch travel egodocuments such as travel diaries and letters. After a prosopographical investigation of all available northern-Netherlandish travel egodocuments created between 1500 and 1915, a selection of these documents is examined in greater detail. In these documents, travellers regarded the possession of identity documents, a correct appearance, and a fitting social identity along with their personal contacts, physical capabilities, and the weather as the most important factors influencing whether they managed to gain access to places. A discussion of these factors demonstrates that no linear increase, nor a decrease, occurred in the spatial power felt by travellers. The exclusion many travellers continued to experience was often overdetermined. The largest groups affected by this were women and less educated families. Yet travellers could also play out different access factors against each other. By paying attention to how practices matched hopes and expectations, it is possible to discover how gravely social inequities were really felt by travellers. Perhaps surprisingly, all social groups desired to visit the same types of places. Their main difference concerned the atmosphere of the places where the different groups felt at home. To a large degree this matched travellers' unequal opportunities. Therefore, although opportunities remained strongly unequal throughout the period, this was not always experienced as a problem. Also, in cases where it was, many travellers knew strategies to work around the obstacles created for them.